Land Surface Displacement in Bangkok, Thailand Inferred from Stanford Method for Persistent Scatterers - Anuphao Aobpaet (Lowland Technology International, 2021)
The Interferometric Synthetic Aperture Radar (InSAR) has come into play an important role as a useful tool in the situation of land subsidence monitoring in Thailand. We conduct research studies on the subsidence of Bangkok and its vicinity area using InSAR techniques. We processed 40 Radarsat-2 images from October 25, 2018, to May 25 to 2019, making the observation point at over 400,000 points, which is dense and noble to shows patterns of subsidence areas on a broad scale, with an average pixel density of 55 points per square kilometer and 100 points per square kilometer in the city. The subsidence rate of the ground ranged from -34.20 to +35.70 mm per year. The spatial data obtained from the InSAR technique is consistent and has characteristics that can effectively show the magnitude and the change in the level of groundwater content. We can conclude that the monitoring of land subsidence in Bangkok and its vicinity areas will be effective when using the InSAR technique as it can be processed throughout all seasons and allowing the leveling survey to be spaced out of time.